Hybrid Mechanoresponsive Polymer Wires Under Force Activation. (20th December 2012) - Feng, Hongbin; Lu, Jin; Li, Jinghong; Tsow, Francis; Forzani, Erica; Tao, Nongjian
<x xml:space="preserve">Abstract</x> Force activation is triggered in a stretched polymer wire with color changes produced as a consequence of the molecules undergoing structural and conformational changes. A markedly increased efficiency of force activation is achieved by decreasing the diameter of the wires. The hybrid mechanosensitive polymer wire can function as micro‐ and nanoscale force sensor. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>